Knowledge, attitude and practice of parents regarding pediatric antiepileptic drug therapy - Shaju, Minumaria; Vinayan, Kollencheri Puthenveettil; Abraham, Suja (International Journal of Epilepsy, 2014)
Objectives To evaluate the parental knowledge, attitude and practice (KAP) regarding the antiepileptic medication therapy in childhood.Methods This study was carried out over a period of 10 months in the division of Pediatric Neurology of Amrita Institute of Medical Sciences. The cohort of patients was selected randomly meeting the inclusion and exclusion criteria. Parents' KAP regarding epilepsy and antiepileptic drug therapy was assessed using a questionnaire prepared by the authors and patient adherence towards antiepileptic drug therapy by using Pediatric Epilepsy Self-Management Questionnaire (PEMSQ).Results A total of 123 patients were selected and enrolled in the study. Seventy eight percent of the respondents knew that epilepsy is a brain disorder, while only 6% of them were aware about all the treatment options. The scoring in the domain of “Disease and Treatment Knowledge & Expectations of parents” was found to be significantly low (69.07%) when compared to other domains in the PEMSQ. Although socioeconomic status did not correlate with knowledge score of the parents (p = 0.216), it was significantly related to adherence (p = 0.042).Conclusion In this cohort, even though the parents had a fair knowledge about the nature of epilepsy, they were found to be less aware about its characteristics, causes and prognosis. The awareness about the nature and duration of treatment, its objectives, use of drugs, their side effects and importance of adherence to drug regimen was found to be significantly low with a potential for affecting the therapeutic outcome. Special awareness programs for parents of children with epilepsy may be needed to reduce the knowledge gaps in the management of epilepsy and to ensure compliance and optimal therapeutic outcomes.
Keywords: Awareness; Antiepileptic drugs; Counseling; Pediatric epilepsy